Real-world experience with selinexor-containing chemotherapy-free or low-dose chemotherapy regimens for patients with relapsed/refractory acute myeloid leukemia and myeloid sarcoma - Xiwen Tong; Jie Jin; Bin Xu; Shuai Su; Li Li; Mengyuan Li; Yizhou Peng; Xia Mao; Wei Huang; Donghua Zhang (Frontiers Media S.A., 2023)
Introduction: Treatment of relapsed or refractory acute myeloid leukemia (R/R AML) and myeloid sarcoma (MS) has presented challenges for decades. Studies on selinexor in combination with various standard or intensive chemotherapy regimens for the treatment of R/R AML have demonstrated promising results. This study aimed to evaluate the efficacy and safety of chemotherapy-free or low-dose chemotherapy regimens with selinexor for R/R AML and MS patients.Methods: Ten patients with R/R AML or MS who received chemotherapy-free or low-dose chemotherapy regimens in combination with selinexor at Tongji Hospital from October 2021 to August 2022 were included in this study. The primary endpoint was overall response rate (ORR) and secondary endpoints included complete remission (CR), CR with incomplete hematological recovery (CRi), partial remission (PR), transplantation rate, and safety.Results: All patients were evaluable for response, achieving CR in four (40.0%) patients and CRi in two (20.0%) patients for a total CR/CRi of 60.0%. The ORR was 80.0% when patients with PR were included. Five (50.0%) patients underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT) after treatment with selinexor-containing regimens. At the end of the follow-up, seven (70.0%) patients were alive, and three patients died of transplant-related complications or disease progression. The most frequently reported nonhematologic adverse events (AEs) in patients were grade 1 or 2 asymptomatic hyponatremia.Conclusion: The chemotherapy-free or low-dose chemotherapy regimens in combination with selinexor for R/R AML are feasible and tolerable and provide an opportunity for patients to receive transplantation.